The University Consortium for Catholic Education (UCCE): A Response to Sustain and Strengthen Catholic Education - Smith, Paige A. (Catholic Education: A Journal of Inquiry and Practice, 2007)
This article examines the current and potential contributions of the University Consortium for Catholic Education (UCCE) to both K-12 and higher Catholic education. In order to situate the development of alternative teacher preparation programs, a history of Catholic teacher formation is addressed followed by a brief summary of the existing programs that comprise the UCCE. Attention is given to the essential nature of a Catholic educator’s responsibility to deepen Catholic identity through authentic education in collaboration with the family and how recent college graduates who matriculate in UCCE programs are formed to respond to this task.